PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA, PELATIHAN TERHADAP KINERJA GURU DI YAYASAN PENDIDIKAN NURCAHAYA MEDAN - maria, radikah; ginting, kristi endah ndilosa; yunita, mella (Jurnal Ekonomi Bisnis Manajemen Prima, 2024)
This research aims to determine the influence of the work environment, work discipline and training on the performance of Nurcahaya School teachers. Technique sampling using a saturated sample technique, with the sample size is 21 teachers. Data collection using questionnaires, then processed and analyzed using descriptive and quantitative analysis. The results of this research show that: 1) Work Environment, Discipline Work and training together have a significant effect on the performance of Nurcahaya School teachers. 2) Work Environment, Work Discipline and Training partial positive and significant effect on Nurcahaya School Teacher Performance.